Performance Measurement In Retailing - Soehadi, Agus W. (Forum Manajemen; Vol 13 No 69 (1999): Forum Manajemen Prasetiya Mulya | April 1999, 1999)
This article is designed to develop the performance measurement in retail research. Performance measurement could be categorised into four types of data, which are financial indicators, operational indicators, direct/objective measures and indirect/subjective measure. Based on this categorised, a six-celled satisfactory scheme is developed. This scheme is useful for comparing and contrasting different measurement approaches that had been done by researchers in marketing and retailing area. In retailing area, the author suggest using both objective and subjective measure for financial indicators [Return on Capital Efficiency (ROCE), Return on Sales (ROS)] and operational indicators (labour productivity, space productivity, perceived service quality, customer satisfaction and customer loyalty).